2019
DOI: 10.1111/jth.14401
|View full text |Cite
|
Sign up to set email alerts
|

Sodium‐site in serine protease domain of human coagulation factor IXa: evidence from the crystal structure and molecular dynamics simulations study

Abstract: Consensus sequence and biochemical data suggest a Na+‐site in the factor (F) IXa protease domain. X‐ray structure of the FIXa EGF2/protease domain at 1.37 Å reveals a Na+‐site not observed earlier. Molecular dynamics simulations data support that Na+ ± Ca2+ promote FIXa protease domain stability. Sulfate ions found in the protease domain mimic heparin sulfate binding mode in FIXa. Summary BackgroundActivated coagulation factor IX (FIXa) consists of a γ‐carboxyglutamic acid domain, two epidermal growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 69 publications
(169 reference statements)
0
13
0
Order By: Relevance
“…All modeling attempts resulted in a single structure, with C-scores > 1.4 and TM-scores > 0.9, so, according to I-TRASSER criteria, these are well-known and very reliable models [32]. The structure of the complex between the EGF domains and the catalytic domain was obtained by superposition of the modeled EGF-2 domains with that of the human EGF-2 domain in the most recent high resolution structure of a fragment of human F9 (PDB ID 6MV4 [33]. All models were inspected in VMD [34].…”
Section: Methodsmentioning
confidence: 99%
“…All modeling attempts resulted in a single structure, with C-scores > 1.4 and TM-scores > 0.9, so, according to I-TRASSER criteria, these are well-known and very reliable models [32]. The structure of the complex between the EGF domains and the catalytic domain was obtained by superposition of the modeled EGF-2 domains with that of the human EGF-2 domain in the most recent high resolution structure of a fragment of human F9 (PDB ID 6MV4 [33]. All models were inspected in VMD [34].…”
Section: Methodsmentioning
confidence: 99%
“…The Na + ion at this site in FXa is coordinated to the main-chain carbonyl O atoms of residues 184A, 185, 221A and 224 and two water molecules (Zhang & Tulinsky, 1997). Later, Schmidt et al (2002), Bajaj et al (2006) and Vadivel et al (2019) reported that Na + at a similar site in APC, FVIIa and FIXa, respectively, is coordinated to four carbonyl O atoms (Fig. 7b) and two water molecules.…”
Section: Discussionmentioning
confidence: 86%
“…In addition to a Ca 2+ -binding site, the protease domain also contains an Na + -binding site (Bajaj et al, 2006). Sequence similarity (Dang & Di Cera, 1996) predicts that the Na +binding site in FVIIa is similar to those in FXa (Zhang & Tulinsky, 1997), activated protein C (APC; Schmidt et al, 2002) and FIXa (Vadivel et al, 2019) but not to that in thrombin (Di Cera et al, 1995;Zhang & Tulinsky, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…43 Together with the 180-loop CT , the 220-loop CT comprises a binding site for Na + , which is coordinated to four backbone carbonyl groups, including the one of Lys394{224 CT } substituted in our study. 15,44 We considered the possibility that disruption of the Hbond network might affect Na + -binding and as such could explain reduced FIXa activity. However, the amidolytic activity of neither wild-type FIXa, nor that of the three FIXa mutants displayed any appreciable Na + -dependence under the conditions tested (Figure S4).…”
Section: Discussionmentioning
confidence: 99%